Anxiety Impacts Consent Capacity to Treatment in Alzheimer's Disease - Kato, Yuka; Matsuoka, Teruyuki; Eguchi, Yoko; Iiboshi, Kiyoko; Koumi, Hiroyuki; Nakamura, Kaeko; Okabe, Kayoko; Nakaaki, Shutaro; Furukawa, Toshiaki A.; Mimura, Masaru; Narumoto, Jin (Frontiers in Psychology, 2021)
This study aimed to clarify how behavioral and psychological symptoms of dementia (BPSD) and cognitive function affect the decision-making capacity of persons with Alzheimer’s disease (AD) in a real informed consent situation about anti-dementia drug prescriptions. The participants were 76 patients with AD. We used the MacArthur Competence Assessment Tool to assess the capacity for consent to treatment (MacCAT-T). We simultaneously used the Mini-Mental State Examination, Executive Interview, Executive Clock Drawing Task, Logical Memory I of the Wechsler Memory Scale-Revised (LM I), LM II, and Neuropsychiatric Inventory to assess cognitive function and psychiatric symptoms. We calculated the correlations between the MacCAT-T scores and the demographic, neuropsychological, and psychiatric variables. Once the univariable correlations were determined, we performed simple linear regression analyses to examine if the regression equations were significant. In the final analyses, we incorporated significant variables into stepwise multiple linear regression analyses to determine the most significant predictors of mental capacity. Age (β = −0.34), anxiety (β = −0.27), and LM I (β = 0.26) were significant predictors of “understanding” (adjusted R2 = 0.29). LM Ⅱ (β = 0.39), anxiety (β = −0.29), and education (β = 0.21) were significant predictors of “understanding of alternative treatments” (adjusted R2 = 0.30). Anxiety (β = −0.36) and age (β = −0.22) were significant predictors of “appreciation” (adjusted R2 = 0.18). Age (β = −0.31) and anxiety (β = −0.28) were significant predictors of explained variance in “reasoning” (adjusted R2 = 0.17). Patients with anxiety had lower scores on all five MacCAT-T subscales: “understanding,” without 3.8 [SD = 1.2] vs. with 2.6 [SD = 1.1]; “understanding of alternative treatments,” without 2.9 [SD = 2.2] vs. with 1.3 [SD = 1.8]; “appreciation,” without 2.9 [SD = 1.1] vs. with 1.9 [SD = 1.2]; “reasoning,” without 4.0 [SD = 2.0] vs. with 2.7 [SD = 1.7]; and “expressing a choice,” without 1.9 [SD = 0.4] vs. with 1.5 [SD = 0.6]. Considering the effects of BPSD, cognitive function, and age/education when assessing consent capacity in persons with AD is important. Reducing anxiety may contribute to improved capacity in persons with AD.